Green biogenic sulfur nanoparticles enhance Capsicum annuum (L.) resilience to salt stress by triggering physio-biochemical and genetic repair mechanisms - Alrabie, Hissah; Alsamadany, Hameed; Almoshadak, Ameina S.; Alshamrani, Rahma; El-Zohri, Manal (Frontiers in Plant Science, 2025)
The synthesis of metal nanoparticles is an expanding field of study due to the potential uses in creating new technologies that facilitate the production of crops by improving tolerance against salinity stress. The current study outlined the green synthesis of sulfur nanoparticles (SNPs) using Moringa oleifera (Lam.) leaf extract and its protective role on Capsicum annuum (L.) growth against salinity stress. Using Fourier transform infrared (FT-IR) spectroscopy, transmission electron microscopy (TEM), and X-ray diffraction (XRD), the effective formation of the synthesized SNPs was examined and approved. The results confirmed the purity and morphology of SNPs. Then, SNPs (1, 10, 100 mg/l) were used in nano-priming to alleviate the adverse effects of NaCl (50, 100 mM) on C. annuum seedlings. The findings demonstrated that C. annuum growth parameters were severely lowered by increasing salinity stress level, whereas SNPs treatments enhanced plant growth under both salt levels. The optimum concentration for alleviating salinity stress was 10 mg/l SNPs. 10 mg/l SNPs significantly increased shoot fresh weight, dry weight, chlorophyll content, cell membrane stability and relative water content by 75.4, 77.8, 82.5, 89.5 and 20.9%, while reduced the water and solute potential, Na+/K+ ratio, proline, glycine betaine, malondialdehyde, H2O2 and superoxide anion content by 45.5, 43.2, 27.7%, 18.1, 40.3, 39.3, 35.4 and 34.5% respectively compared to untreated stressed control at 100 mM NaCl. Moreover, SNPs substantially improved, antioxidant enzymes activities and upregulated the expression of some salt-tolerant genes under saline conditions. Under both salinity levels, the genes CaHAK6, CaHAK7, CaDHN3, CaCAT1 and CaPOD recorded maximum expression at 10 mg/l SNPs. Overall, these findings demonstrate the efficiency of green SNPs as a practical approach to alleviate NaCl-induced stress in C. annuum plants by triggering many physiological, biochemical and genetic repair mechanisms. These results offer a sustainable agri-environmental strategy for mitigating salt stress and enhancing crop production in saline environments.